Knowledge about vertical transmission of HIV and associated factors among women living with HIV or AIDS attending antiretroviral therapy clinic, Western Ethiopia. (January 2022) - Balis, Bikila; Assefa, Nega; Egata, Gudina; Bekele, Habtamu; Getachew, Tamirat; Ayana, Galana Mamo; Raru, Temam Beshir; Taye Merga, Bedasa
Background: The United Nations Program on HIV or AIDS has committed to eliminating the vertical transmission of human immunodeficiency virus. However, significant number of newborn and children are acquiring HIV every year. Therefore, the aim of this study was to assess knowledge of mother on vertical transmission of HIV and associated factors among non-pregnant women receiving antiretroviral therapy in the West Wollega, Western Ethiopia. Methods: A facility-based cross-sectional study design was used on a sample of 422 non-pregnant women attending antiretroviral therapy clinic in West Wollega from 26 February to 26 March 2019. Systematic sampling was used to select the study participants. Pretested and structured interviewer-administered questionnaires and telephone interview were used to collect the data. Multivariable logistic regression model was used to identify factors associated with the knowledge of mother on vertical transmission of HIV. Odds ratio along with 95% confidence interval were estimated to measure the strength of the association. Level of statistical significance was declared at p-value less than 0.05. Result: Out of total participants, 94.1% (95% confidence interval: (91.7%, 96.2%)) of them were knowledgeable about vertical transmission of HIV. Urban resident (adjusted odds ratio: 2.36, 95% confidence interval: (1.27, 4.39)), primary school (adjusted odds ratio: 2.94, 95% confidence interval: (1.11, 7.83)), secondary school (adjusted odds ratio: 3.39, 95% confidence interval: (1.53, 7.55)), being on antiretroviral therapy for greater than 2 years (adjusted odds ratio: 2.67, 95% confidence interval: 1.02, 6.99)), and having child living with HIV (adjusted odds ratio: 1.54, 95% confidence interval: (1.07, 3 .83)) were significantly associated with the knowledge of mother on vertical transmission of HIV. Conclusion: The study indicated that 5.9% of the women lack knowledge about vertical transmission of HIV. This knowledge associated with sociodemographic factors, such as residence, educational status, experiences of having child living with HIV, and being on antiretroviral therapy for greater than 2 years. Thus, interventions toward the elimination of new newborn HIV infections should consider these factors.